Elsie's Troubled Times - Finley, Martha (Franklin, Tenn. : Mission City Press, 2000)
As Elsie and Edward experience the joys of parenthood, the Civil War begins and ends, with terrible losses to their families.
Sequel to: Elsie's true love.
Sequel: Elsie's tender mercies.
Keywords: Marriage -- Fiction; War -- Fiction; Christian life -- Fiction; United States -- Fiction -- History -- Civil War, 1861-1865; United States -- Fiction -- History -- Civil War, 1861-1865